2021
DOI: 10.1002/hep.31615
|View full text |Cite
|
Sign up to set email alerts
|

Contrast‐Enhanced Ultrasonography–Based Hepatic Perfusion for Early Prediction of Prognosis in Acute Liver Failure

Abstract: Background and Aims Acute liver failure (ALF) is a rare but dramatic clinical syndrome characterized by massive hepatic necrosis leading to multiorgan failure. It is difficult to predict the outcomes in patients with ALF using existing prognostic models. We aimed to analyze hepatic perfusion using contrast‐enhanced ultrasound and Doppler ultrasound in patients with ALF and investigate its utility as a prognostic biomarker. Approach and Results In this prospective observational study, 208 patients with acute li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 50 publications
(103 reference statements)
1
8
0
Order By: Relevance
“…Solís-Muñoz et al reported that the portal vein velocity was significantly lower in acutely decompensated patients with cirrhosis who developed ACLF than in those who did not develop ACLF ( 46 ). Furthermore, our data are in line with the results of Kuroda et al ( 34 ) who analyzed hepatic perfusion using contrast-enhanced ultrasound (CEUS) in patients with acute liver failure (ALF) and investigated its utility as a prognostic tool ( 47 ). The authors recorded the time interval (TI) between the time to peak of the hepatic artery (HA) and liver parenchyma (LP) by performing CEUS at baseline and after 7 days.…”
Section: Discussionsupporting
confidence: 89%
“…Solís-Muñoz et al reported that the portal vein velocity was significantly lower in acutely decompensated patients with cirrhosis who developed ACLF than in those who did not develop ACLF ( 46 ). Furthermore, our data are in line with the results of Kuroda et al ( 34 ) who analyzed hepatic perfusion using contrast-enhanced ultrasound (CEUS) in patients with acute liver failure (ALF) and investigated its utility as a prognostic tool ( 47 ). The authors recorded the time interval (TI) between the time to peak of the hepatic artery (HA) and liver parenchyma (LP) by performing CEUS at baseline and after 7 days.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, a more detailed evaluation of the risk for disease progression is warranted. We have recently published two studies regarding the identification of patients who may progress to severe disease following the transfer to a liver center 32,33 . In order to improve the prognosis of patients with ALF, management of the patients with ALI, including early identification of the patients, transfer to a live center, intervention based on accurate diagnosis, and detailed evaluation of the risk of disease progression are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of other measures have been suggested as either additional or replacement measures to identify patients who will obtain a survival benefit from liver transplantation. These include the use of CT-based quantification of liver volume loss with a threshold of less than 1000 cm 3 , the presence of more than 75% necrosis in liver biopsy, abnormal contrast-enhanced ultrasound liver perfusion patterns and the elevation of serologic markers of fibrosis as innovative negative prognostic indicators [83,84,85 ▪ ,86].…”
Section: Prognostic Assessment and Liver Transplantationmentioning
confidence: 99%